The City-Logic of Resistance: Subverting Urbicide in the Middle East City. Issue 3 (2nd September 2017) - Stanley, Bruce
Abstract: Most armed conflict today takes place within urban terrain or within an urbanised context. An extreme variant of such armed conflict is violence perpetrated by external state and non-state forces within the city, known as urbicide. Urbicidal violence deliberately strives to kill, discipline or deny the city to its inhabitants by targeting and then reordering the sociomaterial urban assemblage. Civil resistance within urbicidal violence seeks to subvert the emerging alternative sovereign order sought by such forces. It does so by using the inherent logic of the city in order to maintain/restore the community's social cohesion, mitigate the violence, affirm humanity, and claim the right to the city. This paper investigates the city-logic of civil resistance through examples drawn from the recent urbicidal experiences of Middle East cities such as Gaza, Aleppo, Mosul, and Sana'a. Theoretical insights from the conflict resolution literature, critical urban theory, and assemblage thinking inform the argument.